In vivo self-assembled albumin nanoparticle elicit antitumor immunity of PD-1 inhibitor by imaging and clearing tumor-associated macrophages - Yu, Cheng; Hu, Linan; Yu, Qilin; Ren, Yulu; Zhang, Minping; Gao, Lujing; Lyu, Shiyi; Wang, Junli; Xiao, Enhua; Chen, Zhu; Shang, Quanliang; Xu, Pengfei (Frontiers in Chemistry, 2024)
Eliciting anti-tumor immune responses and improving the tumor microenvironment crucial for boosting the effectiveness of anti-PD-1 immunotherapy. Tumor-associated macrophages (TAMs), the primary types of immune cells infiltrating tumors, play a critical role in the formation of an immunosuppressive microenvironment. In this study, we constructed a novel Evans Blue (EB)-based in vivo self-assembled nanocarrier system, mUNO-EB-ICG-Fc@Alb nanoparticles (designated as MA NPs), for targeted imaging and clearance of M2-TAMs to elicit antitumor immunotherapy of PD-1 inhibitor. In vitro experiments demonstrated the specific fluorescence imaging and killing effect of MA NPs on M2-TAMs. In vivo experiments shown that MA NPs-induced chemodynamic therapy (CDT) successfully reversed the tumor immunosuppressive microenvironment (ITM), promoted intratumoral infiltration of T lymphocytes, and ultimately enhancing the anti-tumor immunotherapy effect of PD-1 inhibitors. This study might provide good inspiration for improving the therapeutic efficacy of cancer immunotherapy.